Damped-SOGI-Based Control Algorithm for Solar PV Power Generating System - Singh, Bhim; Kumar, Shailendra; Jain, Chinmay (IEEE transactions on industry applications, 2017)
This paper deals with two-stage solar photovoltaic (PV) system with a damped-second-order generalized integrator (SOGI) algorithm. Proposed topology not only integrates the PV energy to the grid, in addition, it provides the load compensation, power factor correction, and harmonics elimination. Therefore, a double stage system is proposed where the first stage is a dc-dc boost converter, which performs the maximum power point tracking by regulating its duty ratio. For extracting maximum power from the PV array, an incremental conductance-based approach is utilized. Moreover, in the next stage, a voltage source converter (VSC) is utilized. To control the VSC, a damped-SOGI algorithm is used. By using a damped-SOGI-based control algorithm, fundamental active components of load currents are extracted for evaluating the reference grid currents. After comparing reference grid currents with sensed grid currents, switching pulses for the grid tied VSC are produced. A prototype of the proposed system is developed in the laboratory and test results are presented for verification of control of solar photovoltaic system.